2013
DOI: 10.5543/tkda.2013.18488
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of atrial fibrillation in Turkey: preliminary results of the multicenter AFTER study

Abstract: These results demonstrate the necessity for improved quality of physician care of patients with AF, especially with regards to antithrombotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…The TTR values may vary between countries in patients VKA therapy ( 7 , 8 ). In our country, the rate of TTR is lower than expected, and differences between geographical regions remain unknown for the time being ( 9 , 10 , 11 ). However, the ROCKET-AF study reported that TTR rates may vary among geographical regions ( 12 ).…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…The TTR values may vary between countries in patients VKA therapy ( 7 , 8 ). In our country, the rate of TTR is lower than expected, and differences between geographical regions remain unknown for the time being ( 9 , 10 , 11 ). However, the ROCKET-AF study reported that TTR rates may vary among geographical regions ( 12 ).…”
mentioning
confidence: 61%
“…Previous studies in Turkey noted low TTR values in this country. The AFTER study, which included 2242 patients with at least one AF attack from 17 different centres in Turkey, reported non-valvular AF (NVAF) and effective INR levels as 78% and 41.3%, respectively ( 10 ). In the WATER (Warfarin in Therapeutic Range) study, the mean TTR value was 42.3%±18 in 572 patients with AF (71% NVAF) during 22-month follow-up ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the AFTER study, it was shown that the TTR level was detected in 41.3% of the patients with AF in Turkey (16). On the other hand, patients treated with warfarin were outside the INR target range 32.1% of the time in British population (3).…”
Section: Discussionmentioning
confidence: 99%
“…There are several predictors of PAF, such as hypertension, heart failure, valvular heart disease, and hyperthyroidism (14, 15). In our previous multicenter study, the Atrial Fibrillation Registry in Turkey (AFTER), we found that hypertension was the most common comorbid condition in patients with AF (16, 17). In fact, an increased P wave duration on standard 12-lead ECG indicates the presence of an atrial conduction disorder (18).…”
Section: Discussionmentioning
confidence: 99%